A Comparison Of The AHP And MOORA Methods In Determining Recipients Of Free Nutritious Food In Ujung Serdang Village - Nera Mayana Br Tarigan; Dameria Esterlina Br Sijabat; Nurika Sari Siregar; Shadiq Arif Musyaffa (Jurnal Armada Informatika, 2026)
The Free Nutritious Food Program (MBG) is one of the government’s efforts to improve the nutritional quality of the population, particularly for vulnerable groups such as toddlers, pregnant women, and breastfeeding mothers. However, the process of determining aid recipients often faces challenges due to the large number of potential recipients and the variety of criteria that must be considered, which can potentially lead to subjectivity in decision-making. This study aims to compare the Analytical Hierarchy Process (AHP) and Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) methods in determining recipients of the Free Nutritious Food program in Ujung Serdang Village. The data used consisted of 100 community members assessed based on five criteria: household income, number of dependents, nutritional status, housing conditions, and other assistance previously received. The AHP method was used to determine the priority weights of the criteria, while the MOORA method was used to rank the alternatives. The results showed that the “Nutritional Status” criterion had the highest weight at 0.488, followed by “Family Income” at 0.240, “Number of Dependents” at 0.136, “Housing Conditions” at 0.090, and “Other Assistance” at 0.046. The ranking results show that alternative A085 ranked first in both methods. The AHP method identified 60 viable alternatives and 40 non-viable ones, while the MOORA method identified 39 viable alternatives and 61 non-viable ones. The research results indicate that the MOORA method is more selective and objective in determining aid recipients; therefore, it is recommended to support a more targeted distribution process for the Free Nutritious Food program.